Oil spill cleanup using EDTA-coated magnetite magnetic nanoparticles - Awda, Maha J.; Abdulmajeed, Basma A.; Shareef, Zaid Nidhal (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
As a result of the critical importance of crude oil in modern industrial society, oil spills, specifically those involving crude oil, generate substantial environmental and ecological difficulties. In contrast to conventional treatment approaches, nanotechnology has demonstrated its efficacy in remedying oil spills This type of pollution could occur during oil investigation, transit, or storage. This study adopted a straightforward and economical method utilizing iron oxide magnetic nanoparticles for oil spills cleanup. Magnetite Fe3O4 MNPs were synthesized using the co-precipitation technique, which involved combining ferric and ferrous ions in an alkaline solution at 80°C and a pH of 14. MNPs were characterized using X-ray diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and vibrating sample magnetometer (VSM). To improve their stability and efficacy, MNPs were coated with ethylenediaminetetraacetic acid (EDTA). Three samples of crude oil with different APIs (23, 28.4, and 40.3) were used to study the ability of coated MNPs for oil spill cleanup. Removal experiments were conducted at 25°C with a mass range of adsorbent (0.02-0.06 g). A neodymium magnet was utilized to extract the oil-contaminated magnetic nanoparticles from the water. The gravimetric oil removal (GOR) for APIs 23, 28.4, and 40.3 were 11.4 - 3.35, 7.19- 2.15, and 4.81 to 1.16 g/g, respectively. Experimental results demonstrated an inverse relationship between GOR and the API value, indicating that as the API value decreased, GOR increased, and vice versa. Furthermore, as the mass of the adsorbent material increased (0.02-0.06g), the GOR value decreased.